Pengaruh Model Pembelajaran Berbasis Project Based Learning Terhadap Hasil Belajar Sejarah Siswa Kelas XI IPA MAN 3 Medan - Vinny Zannatil Wanzi Pradara Siregar; Meliana Aini; Siti Kholiza Panjaitan; Rezki Milleandi; Syarifah Syarifah (Program Studi Pendidikan Biologi, 2022)
This study discusses the influence of the use of project-based learning models on history learning on the learning outcomes of class XI IPA MAN 3 Medan students. The approach taken in this study is a quantitative approach of the type of quasi-experimental design. The population in this study is students of class XI IPA MAN 3 Medan for the 2022/2023 school year, the sample in this study is class XI IPA 1, this sampling procedure uses a random sample technique . The variables in this study are the Project Based Learning learning model and learning outcomes. The data collection method uses test methods, questionnaires and documentation. Research shows that, the learning outcomes of students who use the Project Based Learning model have an average pretest score of 61.86 and posttests increased by 82.94. There is an influence on the use of Project Based Learning learning models to the results of learning history. This is seen from the magnitude of the influence of the use of the project-based learning model is 23.8%, this shows that the use of the project-based learning learning model is a fairly dominant factor in determining whether or not learning outcomes increase.